Protein Lactylation Critically Regulates Energy Metabolism in the Protozoan Parasite Trypanosoma brucei - Zhang, Naiwen; Jiang, Ning; Yu, Liying; Guan, Tiandong; Sang, Xiaoyu; Feng, Ying; Chen, Ran; Chen, Qijun (Frontiers in Cell and Developmental Biology, 2021)
Lysine lactylation has been recognized as a novel post-translational modification occurring on histones. However, lactylation in non-histone proteins, especially in proteins of early-branching organisms, is not well understood. Energy metabolism and the histone repertoire in the early-diverging protozoan parasite Trypanosoma brucei, the causative agent of African trypanosomiasis, markedly diverge from those of conventional eukaryotes. Here, we present the first exhaustive proteome-wide investigation of lactylated sites in T. brucei. We identified 387 lysine-lactylated sites in 257 proteins of various cellular localizations and biological functions. Further, we revealed that glucose metabolism critically regulates protein lactylation in T. brucei although the parasite lacks lactate dehydrogenase. However, unlike mammals, increasing the glucose concentration reduced the level of lactate, and protein lactylation decreased in T. brucei via a unique lactate production pathway. In addition to providing a valuable resource, these foregoing data reveal the regulatory roles of protein lactylation of trypanosomes in energy metabolism and gene expression.